Paraplegia and intracranial hypertension following epidural anesthesia: report of four cases - Frederico A. D. Kliemann (Arquivos de Neuro-Psiquiatria)
Four patients who received epidural anesthesia presented sustained myelopathy; three of them had complete paraplegia and one a lumbo-sacral myelopathy with urinary retention. All four patients complained of very intense radicular pains immediately after the analgesic effect of Lidocaine was over. Two patients in whom lumbar puncture was done in the first 24 hours presented an aseptic meningitic reaction in CSF. Paraplegia completed in two to ten months in three patients and in two of them severe intracranial hypertension developped at this time. It is proposed that the disease runs a two-stages course, at least in some cases, characterized by an aseptic meningitis, followed, after a silent period of some months, by signs of adhesive spinal and intracranial arachnoiditis. Intracranial hypertension was controlled by ventriculo-peritoneal shunt; in two patients a transitory effect of intrathecal injections of methyl-prednisolone acetate was observed. Two patients recovered almost completely from paraplegia.